ЎРТА ОСИЁ ДАВЛАТ УНИВЕРСИТЕТИ (САГУ) ОЛИМЛАРИНИНГ ПОМИРГА УЮШТИРИЛГАН ЭКСПЕДИЦИЯЛАРДАГИ ИШТИРОКИ (1923-1928 йиллар) - Кенжаева, Н.С. (SCIENCE and SOCIETY, 2020)
The paper deals with the study of the territory of the Pamirs expeditions of the USSR Academy of Sciences in the period 1923-1928, and the participation of scientists from SAGU. The author reviews the principal directions explore the region. It is shown how the preparation of expeditions took place. In addition, the main scientific results and the results of the expeditions were studied.
Keywords: Pamir; expedition; Tajikistan; Academy of Sciences of the USSR; Central Asian State University